Os quatro epigramas para flauta solo de Cláudio Santoro: do manuscrito (1942) à edição (1975) - Rafael Ribeiro Ferreira (2012)
Four Epigrams for flute solo were composed in 1942 by Claudio Santoro. At this time, the composer was engaged in an important group whose goal was the articulation of new music composed in Brazil, the Musica Viva Group. Student of Koellreuter's, Santoro uses twelvetones techniques and effects extended techniques for the flute. This research proposes to investigate the extended techniques and relate their use to other pieces for solo flute composed in the 20th century along with suggestions and contributions to the interpretation of the work. The first chapter focuses on investigating historical and asthetical contexts of the composer and Four Epigrams. In the second chapter the subjects are the relation of the piece and other selected works and a comparison of the edition with the manuscript. In the last chapter an analyzes of Four Epigrams is presented.